2020
DOI: 10.1155/2020/1216926
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 Inhibits Fibrosis via Wnt/β‐Catenin Pathways during the Process of Angiogenesis in Human Umbilical Vein Endothelial Cells

Abstract: Although SDF-1/CXCR7 plays an important role in angiogenesis, the function and the pathway of the SDF-1/CXCR7 axis might depend on the cell type or tissue origin and not fully understood. In this study, we investigated the effect of CXCR7 in SDF-1-induced proliferation, migration, apoptosis, tube formation, and endothelial-to-mesenchymal transition (EndMT) of human umbilical vein endothelial cells (HUVECs), and the potential pathway of SDF-1/CXCR7. We confirmed that the silencing of CXCR7 inhibited the prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
3
5
1
Order By: Relevance
“…Notably, at 24 h, we observed a dose-dependent effect on wound healing, with the fastest migration occurring at 100 ng/mL, with a healing rate of 61.51% when compared to 37.50%, 53.81%, and 46.13% for the 0, 200, and 400 ng/mL groups, respectively. These finding are similar to those observed from Shen et al 66 Kuhlmann et al 67 identified that SDF-1 could promote endothelial cell migration by activating the Ca 2+ -activated K + channel with large conductance, therefore, it is likely a similar mechanism to enhance migration was activated in our study.…”
Section: Exploration Of the Optimum Loading Concentration Of Sdf-1supporting
confidence: 93%
See 1 more Smart Citation
“…Notably, at 24 h, we observed a dose-dependent effect on wound healing, with the fastest migration occurring at 100 ng/mL, with a healing rate of 61.51% when compared to 37.50%, 53.81%, and 46.13% for the 0, 200, and 400 ng/mL groups, respectively. These finding are similar to those observed from Shen et al 66 Kuhlmann et al 67 identified that SDF-1 could promote endothelial cell migration by activating the Ca 2+ -activated K + channel with large conductance, therefore, it is likely a similar mechanism to enhance migration was activated in our study.…”
Section: Exploration Of the Optimum Loading Concentration Of Sdf-1supporting
confidence: 93%
“…Meanwhile, there was no statistical difference between the different SDF-1 concentrations tested (P > 0.05). Although Shen et al showed that 100 ng/mL SDF-1 could promote HUVECs proliferation within 24 h, 66 our result suggested that SDF-1 tended to stimulate HUVECs proliferation on the first day, and the effect was significant on the second and third day. These differential results may be due by different cell states, environments, and culture mediums used.…”
Section: Exploration Of the Optimum Loading Concentration Of Sdf-1contrasting
confidence: 92%
“…Consistent with this, we found that CXCL12 activation of CXCR4 -but, interestingly, not CXCR7 -is required for CXCL12-induced upregulation of master transcription factor, Slug, which drives partial EndoMT during angiogenesis (Hultgren et al, 2020). By contrast, others have reported that CXCL12 activation of CXCR7 induces Wnt signaling to inhibit EndoMT-associated fibrosis (Shen et al, 2020).…”
Section: Regulatory Mechanisms That Govern the Endomt Program Signaling Pathways Regulating Endomtsupporting
confidence: 84%
“… 58 In a previous study, we reported that Wnt/β-catenin signaling suppression alleviates vascular fibrosis. 59 Together, the above findings suggest that Wnt/β-catenin signaling activation might play a critical role in CNV pathogenesis. Intriguingly, the Notum promoter was methylated and Wnt/β-catenin signaling was hyperactivated in laser-induced CNV tissues or VEGFA-stimulated ECs, as demonstrated above.…”
Section: Discussionmentioning
confidence: 82%